Preventive surgery against aspiration for a patient with uncurable esophagus cancer - IWASAKI, Shin-ichi; SATO, Shintaro; SUZUKI, Motohiko; MURAKAMI, Shingo; TOYOTA, Kiichi; ESAKI, Shin-ichi (jibi to rinsho, 2020)
Aspiration pneumonia occurs in patients with severe neurodegenerative disease and neurovascular disease, as well as occurs in patients with head and neck cancer, esophagus cancer, and lung cancer. Preventive surgery against aspiration is usually performed for patients with severe neurological disease, but is rarely done for patients with untreatable cancer. We herein report a case of preventive surgery against aspiration for a patient with unresectable cancer. A 62-year-old man with stage IV esophagus cancer underwent esophageal-gastric bypass surgery to allow him to eat while avoiding obstruction due to the tumor mass. However, since the cancer had already induced bilateral recurrent laryngeal nerve palsy, he always suffered from aspiration pneumonia. His repetitive pneumonia stopped after surgery with subglottic laryngeal closure. He was then able to eat food without any concerns regarding aspiration pneumonia. He ultimately died of esophageal cancer six months after undergoing preventive surgery. However, the patient's quality of life clearly improved after undergoing preventive surgery.